(untitled) (International Journal of Environmental Sciences, 2025)
The experimental material comprising 30 genotypes including two checks were evaluated in Randomized Block Design during two crop seasons i.e., Kharif -2022 and Rabi-2022-23 at two locations i.e., Parbhani and Nanded comprising three different environments viz., E1 (Parbhani Kharif-2022), E2 (Nanded Kharif-2022) and E3 (Nanded Rabi-2022-23). Data were recorded on twelve quantitative characters viz., days to 50% flowering, days to first harvest, number of ridges per fruit, number of fruits per plant, fruit length, fruit girth, fruit weight, plant height, number of nodes per plant, internodal length and fruit yield per plant. Analysis of variance pooled over environment also revealed significant differences among genotypes for all the characters indicated significance variation among the genotypes irrespective of environment. Similarly, significant mean sum of squares due to environment was found in the expression of all the traits. Estimates of environmental indices revealed that kharif 2022 at Nanded (E2) was proved to be best environment to realize increase in fruit yield per plant. Similarly, kharif Parbhani 2022 (E1) was also noticed better for expression of number of ridges per fruit, number of fruits per plant, fruit girth, number of nodes per plant and plant height. The study of stability parameters indicated that the genotype IC-9856 were identified as average stable for fruit yield per plant also found to be average stable for one or more yield contributing traits across the environments. The maximum number of genotypes have shown better environment stability for the characters like number of ridges per fruit, fruit weight, fruit length, fruit girth, number of nodes per plant and number of branches per plant.